A Rare Appendiceal Neoplasm Presenting as Chronic Appendicitis in an Elderly Female: A Case Report - Perdana, Rizqy Khairi; Nugraha, Rifki Akbar (Lembaga Teewan Journal Solutions, 2026)
Appendiceal neoplasms are rare lesions with nonspecific clinical manifestations that frequently resemble acute or chronic appendicitis, resulting in delayed or incidental diagnosis. Low-grade appendiceal mucinous neoplasm (LAMN) is an uncommon epithelial tumor characterized by mucin production and cystic dilatation of the appendix, with potential progression to pseudomyxoma peritonei if rupture occurs. A 65-year-old woman presented with intermittent right lower quadrant abdominal pain persisting for approximately one year, accompanied by occasional nausea and reduced appetite. Physical examination revealed localized tenderness without peritoneal signs, while laboratory findings were unremarkable except for mild neutrophilia. Abdominal ultrasonography demonstrated appendiceal dilatation with appendicolith, leading to a preoperative diagnosis of chronic appendicitis. An elective appendectomy was performed. Intraoperatively, the appendix appeared markedly enlarged and cystically dilated, forming a tumoral mass suspicious for appendiceal neoplasm. Histopathological examination demonstrated mucinous columnar epithelium with low-grade dysplasia, intraluminal mucin accumulation, and absence of destructive stromal invasion, confirming LAMN. The postoperative course was uneventful with significant symptomatic improvement. LAMN should be considered in elderly patients presenting with chronic right lower quadrant pain resembling chronic appendicitis. Careful surgical handling and routine histopathological examination are essential to establish an accurate diagnosis and prevent complications such as pseudomyxoma peritonei.